Silicon and selenium fertilizer management improved productivity and aroma of fragrant rice. Issue 2 (22nd December 2020) - Du, Bin; Wang, Wenxi; Jiang, Shuochen; Xie, Yimei; Cheng, Yinjie; Xu, Jianlong; Xing, Danying
Abstract: Both Si and Se are the nutrient elements which had significant effects on crop growth and development. However, the application of Si and Se fertilizer management in field production of fragrant rice ( Oryza sativa L.) was rarely reported. The present study was conducted with the objective to explore the effects of Si and Se fertilizer on fragrant rice performance though a six‐season field experiment. The Se rates were set at three levels: 0 g ha −1 (Se0), 36 g ha −1 (Se1), and 72 g ha −1 (Se2). The SiO2 rates were set at three levels: 0 kg ha −1 (Si0), 22.45 kg ha −1 (Si1), and 45 kg ha −1 (Si2). Compared with Si0Se0 treatment, Si and Se treatments significantly increased SPAD values and net photosynthetic rates of fragrant rice at tillering stage and heading stage. Higher grain yield, effectively panicle number and seed‐setting rate were also recorded in Si1Se1, Si1Se2, Si2Se1, and Si2Se2 treatments than Si0Se0 treatment in each cropping season. Moreover, Si and Se fertilizer management significantly increased the grain 2‐acetyl‐1‐pyrroline (2‐AP, main component of fragrant rice aroma) concentrations and the Si2Se1 treatment produced the highest or equally highest grain 2‐AP concentration in each cropping season. Core Ideas: Selenium and Si fertilizer increased the grain yield of fragrant rice. Selenium and Si fertilizer promote 2‐acetyl‐pyrroline concentration of fragrant rice. Selenium and Si fertilizer increased photosynthetic rate of fragrant rice.